2012
DOI: 10.1111/j.1756-185x.2012.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulsed electromagnetic field therapy in the management of patients with discogenic lumbar radiculopathy

Abstract: PEMF therapy is an effective method for the conservative treatment of lumbar radiculopathy caused by lumbar disc prolapse. In addition to improvement of clinically observed radicular symptoms, PEMF also seems effective in reducing nerve root compression as evidenced by improvement of SSEP parameters after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 20 publications
0
32
1
3
Order By: Relevance
“…On the other hand, several recent studies showed the effectiveness of the PEMF treatment in clinical assessment of arthritis, osteoarthritis or sciatica, or neuropathy [Weintraub and Cole, ; Graak et al, ; Ozguclu et al, ; Omar et al, ]. Despite evidence of clinical effectiveness, the exact physiological impact of PEMF in a sufficient strength (of the electromagnetic field) in the case of osteoarthritis has still not been fully explored and requires further examination—this is true especially for applied frequencies, flux densities, and therapy periods.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several recent studies showed the effectiveness of the PEMF treatment in clinical assessment of arthritis, osteoarthritis or sciatica, or neuropathy [Weintraub and Cole, ; Graak et al, ; Ozguclu et al, ; Omar et al, ]. Despite evidence of clinical effectiveness, the exact physiological impact of PEMF in a sufficient strength (of the electromagnetic field) in the case of osteoarthritis has still not been fully explored and requires further examination—this is true especially for applied frequencies, flux densities, and therapy periods.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic therapy has a long history in the treatment of various medical conditions to improve the recovery of various health problems [26]. Doctors from Greece, China, Japan, and Europe successfully used the magnet in their practice to treat patients [15].…”
Section: Pulsed Electromagnetic Field Stimulationmentioning
confidence: 99%
“…In addition to radicular pain, 9 of 16 studies also used the term sciatica to represent their participants with radiating leg pain, while 4 studies also used the term radiculopathy . Two studies that used both the terms radicular pain and radiculopathy included symptom‐related (pain distribution) and sign‐related (neurological deficits) eligibility criteria (Khoromi et al., , ), concurring with the IASP taxonomy, while the other two only required symptom‐related but not sign‐related criteria (Keynan et al., ; Omar et al., ).…”
Section: Resultsmentioning
confidence: 99%